Single resonator microwave device for monitoring the complex dielectric constant of liquid fuels and lubricants - Zhukov, B.V.; Borbulev, S.I. (Radiotekhnika, 2020)
A simplified structural diagram of a single-cavity microwave dielectric meter designed to control the complex permittivity of liquid fuels and lubricants is presented. The structural diagram of the microwave sensor of the dielectrometer, made in the form of a parallelepiped, inside which waveguide paths, a resonator, controlled and reference generators, mixing and detector diodes and attenuators is considered. A general view of the lower part of the microwave sensor housing is given. The technique of initial tuning of the microwave sensor is considered, during which the initial frequencies of the controlled and reference oscillators are set and the range of electronic frequency tuning of the frequency of the controlled generator is determined. A method for calibrating a dielectrometer with an empty cuvette is presented. This method makes it possible to determine the suitability of the cuvette for its use in measuring the complex dielectric constant of samples of fuels and lubricants, and to exclude the influence of the dispersion of the dielectric constant of the material of the cuvette on the results of measuring the complex dielectric constant of fuels and lubricants. The technique of studying the parameters of samples of fuels and lubricants is considered, based on which the measurement data are presented on a complex plane for analyzing the results obtained. A technique for studying the difference between a fuel and lubricant sample and its standard is presented, which includes measuring the parameters of an empty cell, measuring the real and imaginary components of the complex dielectric constant of the fuel and lubricant sample and its standard, and analyzing the differences between their real and imaginary components on a complex plane.